Prognosis and immune infiltration analysis of endoplasmic reticulum stress-related genes in bladder urothelial carcinoma - Wang, Yaxuan; Zhu, Haixia; Wang, Xiaolin (Frontiers in Genetics, 2022)
Background: Abnormal activation of endoplasmic reticulum stress sensors and their downstream signaling pathways has become a key regulator of tumor growth and metastasis as well as the response to chemotherapy, targeted therapy and immunotherapy. However, the study of endoplasmic reticulum stress on immune microenvironment of BLCA is still insufficient. Methods: Firstly, 23 ER stress genes were selected to analyze their expression differences and prognostic value in BLCA based on the existing BLCA genome atlas data. According to the expression level of ER stress genes in BLCA, two independent clusters were identified by consensus cluster analysis, and then the correlation between these two clusters and immune microenvironment and their prognostic value were analyzed. Finally, we analyzed the prognostic value of endoplasmic reticulum stress key gene HSP90B1 in BLCA and the mechanism that may affect the immune microenvironment. Results: Two independent clusters identified by consensus clustering showed a worse prognosis and higher expression of immunoassay site-related genes (CD274, PDCD1, CTLA4, HAVCR2, LAG3, PDCD1LG2 and TIGIT) in cluster 1 compared with cluster 2. In addition, both TIMER and CIBERSORT algorithms showed that the expression of immune infiltrating cells in cluster 1 was significantly higher than that in cluster 2. Subsequently, HSP90B1 was identified as a key er stress gene in BLCA, and its high expression indicated poor prognosis and was closely related to PD1. We also analyzed the correlation between HSP90B1 expression and immune-infiltrating cell related biomarkers, and obtained positive results. Finally, we verified the prognostic value of HSP90B1 in BLCA by immunohistochemical assay in tissue microarray of 100 patients with BLCA, and confirmed that HSP90B1 can be used as a prognostic biomarker in BLCA patients Conclusion: Our study suggests that er stress plays a key role in the BLCA immune microenvironment, and HSP90B1 is a potential novel prognostic biomarker and a potential target for cancer immunotherapy.